Studies of the ATPase activity of the ABC protein SUR1. - De Wet, H; Mikhailov, M; Fotinou, C; Dreger, M; Craig, T; Vénien-Bryan, C; Ashcroft, F (2007)
The ATP-sensitive potassium (K(ATP)) channel couples glucose metabolism to insulin secretion in pancreatic beta-cells. It comprises regulatory sulfonylurea receptor 1 and pore-forming Kir6.2 subunits. Binding and/or hydrolysis of Mg-nucleotides at the nucleotide-binding domains of sulfonylurea receptor 1 stimulates channel opening and leads to membrane hyperpolarization and inhibition of insulin secretion. We report here the first purification and functional characterization of sulfonylurea receptor 1. We also compared the ATPase activity of sulfonylurea receptor 1 with that of the isolated nucleotide-binding domains (fused to maltose-binding protein to improve solubility). Electron microscopy showed that nucleotide-binding domains purified as ring-like complexes corresponding to approximately 8 momomers. The ATPase activities expressed as maximal turnover rate [in nmol P(i).s(-1).(nmol protein)(-1)] were 0.03, 0.03, 0.13 and 0.08 for sulfonylurea receptor 1, nucleotide-binding domain 1, nucleotide-binding domain 2 and a mixture of nucleotide-binding domain 1 and nucleotide-binding domain 2, respectively. Corresponding K(m) values (in mm) were 0.1, 0.6, 0.65 and 0.56, respectively. Thus sulfonylurea receptor 1 has a lower K(m) than either of the isolated nucleotide-binding domains, and a lower maximal turnover rate than nucleotide-binding domain 2. Similar results were found with GTP, but the K(m) values were lower. Mutation of the Walker A lysine in nucleotide-binding domain 1 (K719A) or nucleotide-binding domain 2 (K1385M) inhibited the ATPase activity of sulfonylurea receptor 1 by 60% and 80%, respectively. Beryllium fluoride (K(i) 16 microm), but not MgADP, inhibited the ATPase activity of sulfonylurea receptor 1. In contrast, both MgADP and beryllium fluoride inhibited the ATPase activity of the nucleotide-binding domains. These data demonstrate that the ATPase activity of sulfonylurea receptor 1 differs from that of the isolated nucleotide-binding domains, suggesting that the transmembrane domains may influence the activity of the protein.